DAMPAK PENERAPAN BIMBINGAN KELOMPOK DENGAN TEKNIK KONTRAK PRILAKU DALAM MEREDUKSI PROKRASTINASI SISWA SMP - Ikshan Adi Pratama, Muhammad; Dida Firmansyah; Desy Susanti (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
Procrastination, or the habit of procrastinating, is a common phenomenon among individuals of all ages and educational levels. Although considered a harmful habit, procrastination is a complex and multifaceted topic, which involves psychological, social and environmental factors.  The purpose of this study is to determine the impact of the application of group guidance with behavior contract techniques in reducing procrastination of junior high school students. The method used in this research is quasi experiment with nonequivalent control group design. The samples of this study were 7th, 8th, and 9th grade students at SMP Plus Anwarul Huda. The students involved were 20 students who were divided into two groups, namely the experimental group and the control group. Based on the results of the Independent Sample T-Test test. The N-Gain test shows that group guidance with behavior contract techniques has an impact in reducing procrastination with a significant value (2-tailed) of 0.012 <0.05 and the N-Gain Score results show the average result for the experimental class of -1.004 and the average group class is -0.061. With this reduction in procrastination, it can be stated that group guidance with behavior contract techniques has an impact in reducing academic procrastination.